NKp46 Clusters at the Immune Synapse and Regulates NK Cell Polarization - Hadad, Uzi; Thauland, Timothy J.; Martinez, Olivia M.; Butte, Manish J.; Porgador, Angel; Krams, Sheri M. (Frontiers in Immunology, 2015)
Natural killer cells play an important role in first-line defense against tumor and virus-infected cells. The activity of NK cells is tightly regulated by a repertoire of cell-surface expressed inhibitory and activating receptors. NKp46 is a major NK cell activating receptor that is involved in the elimination of target cells. NK cells form different types of synapses that result in distinct functional outcomes: cytotoxic, inhibitory, and regulatory. Recent studies revealed that complex integration of NK receptor signaling controls cytoskeletal rearrangement and other immune synapse-related events. However the distinct nature by which NKp46 participates in NK immunological synapse formation and function remains unknown. In this study we determined that NKp46 forms microclusters structures at the immune synapse between NK cells and target cells. Over-expression of human NKp46 is correlated with increased accumulation of F-actin mesh at the immune synapse. Concordantly, knock-down of NKp46 in primary human NK cells decreased recruitment of F-actin to the synapse. Live cell imaging experiments showed a linear correlation between NKp46 expression and lytic granules polarization to the immune synapse. Taken together, our data suggest that NKp46 signaling directly regulates the NK lytic immune synapse from early formation to late function.